Groundspeed - Phillips, Emilia (Book collections on Project MUSE., 2016)
Groundspeed moves and doesn't stop moving. From pastorals on American highways to self-reckonings after a cancer diagnosis to examinations on grief and transience after the death of a brother, this collection of poems asks readers not only to size up threats but anxieties. Phillips witnesses a small plane crash and examines roadside attractions. She reckons with sexuality after a partner asks for a threesome, and renders a candid portrait of a nude, post-surgery body in a mirror. In this raw and personal book, Phillips insists upon one's own preservation through and beyond grief and trauma with the warning creation is only myth; destruction narrative.